Credit Risk in Agriculture Sector - Mishra, Rabindra Kumar (Journal of Commerce and Trade, 2012)
The objective of the research paper is to study the credit deficit in agricultural sector. Credit deficit in agricultural sector means the difference between the institutional farm credit availed by the farmers and cost of production. Farmers require access to affordable, adequate and timely credit to purchase and use the inputs required for cultivation. But the credit provided by the financial institutions to agricultural sector continues to be inadequate and less than the cost of production. It compels them to depend on informal sources of credit. So, in this paper in order to examine the difference between institutional short term credit availed by the farmers and cost of production i.e. credit deficit per acre and per farms, a field study (2009-10) of three villages of different degree of Bargarh district (Orissa) India has been done. In order to test the hypotheses to know the significant difference in the credit deficit per acre and per farm across the villages and farm sizes TWO WAY ANOVA TEST has been done.